2020
DOI: 10.5455/medarh.2020.74.153-155
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Acute Intermittent Porphyria as a Cause of Spontaneous Abortion

Abstract: Introduction:The association of acute intermitetn porphyria (AIP) with pregnancy and as a cause of spontaneous abortion is rare. Aim: To show a case of AIP known before pregnancy in a patient who had a spontaneous abortion. Case report: A gynecologist examined 26-yearold patient in the 8th week of gestation, due to initial spontaneous abortion, abdominal pain, constipation, muscle weakness, vomiting and dark colour of urine. Her therapy was dydrogesterone. In consultation with an anesthesiologist, a short intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…β‐estradiol and norgestrel were used to represent the estrogen and progestogen classes, respectively, and we found that, at higher concentrations, both led to a notable accumulation of PP, especially in the presence of DFO (Figure 2). Norgestrel, however, produced greater fluorescence readings than β‐estradiol, which is in keeping with clinical impressions and observations in human subjects 2,47–52 . We also tested alpha‐methyldopa because it continues often to be used to control systemic arterial hypertension in pregnant women.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…β‐estradiol and norgestrel were used to represent the estrogen and progestogen classes, respectively, and we found that, at higher concentrations, both led to a notable accumulation of PP, especially in the presence of DFO (Figure 2). Norgestrel, however, produced greater fluorescence readings than β‐estradiol, which is in keeping with clinical impressions and observations in human subjects 2,47–52 . We also tested alpha‐methyldopa because it continues often to be used to control systemic arterial hypertension in pregnant women.…”
Section: Discussionsupporting
confidence: 70%
“…Norgestrel, however, produced greater fluorescence readings than β‐estradiol, which is in keeping with clinical impressions and observations in human subjects. 2 , 47 , 48 , 49 , 50 , 51 , 52 We also tested alpha‐methyldopa because it continues often to be used to control systemic arterial hypertension in pregnant women. Although the drug had a low CC 50 of 0.164 mM in the presence of DFO, it did not lead to an appreciable accumulation of PP below concentrations that led to appreciable cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient reported more frequent porphyric attacks during her menstrual cycles, specifically around ovulation, which is a common finding among women with AIP. Estrogen and progesterone induce ALAS‐1, increasing the levels of porphyrin intermediates, which play a role in causing acute attacks 9,10 . This is further supported by results of a recent study that used an in vitro drug fluorescence screening assay to test for porphyrogenicity; both β‐estradiol and norgestrel, drugs in the estrogen and progestogen classes, respectively, led to a significant accumulation of protoporphyrins 11 .…”
Section: Discussionmentioning
confidence: 64%
“…Estrogen and progesterone induce ALAS-1, increasing the levels of porphyrin intermediates, which play a role in causing acute attacks. 9,10 This is further supported by results of a recent study that used an in vitro drug fluorescence screening assay to test for porphyrogenicity; both β-estradiol and norgestrel, drugs in the estrogen and progestogen classes, respectively, led to a significant accumulation of protoporphyrins. 11 Our patient continued to have low ALA and PBG even during her menstrual cycles, so it is still unclear what the etiology and pathogenesis are for her ongoing symptoms.…”
Section: Discussionmentioning
confidence: 73%